Numerical and Species Composition of Insects Transmitting Viral Infection in North Ossetia - Gerieva Fаtima; Gazdanova, Irina; Basiev, Soltan (KnE Life Sciences, 2021)
One of the major tasks in the production of original and elite potato seeds is to prevent the rapid re-infection of the healthy material with viruses in the open field. The high rate of infection with each subsequent reproduction reduces seed productivity and worsens the tuber varietal quality. Currently, about two dozen viruses that infect potatoes have been identified. In the field, most of the harmful viruses of potatoes are transmitted by insects such as aphids, cicadas and bedbugs. The purpose of our research was to study the species composition of transmitters and the intensity of their flight in North Ossetia. Studying the activity of the winged aphid vector is a prerequisite for the implementation of protective measures against re-infection of the sanitized material with viruses. The most important criteria characterizing aphids in transferring potato viruses during the growing season were as follows: the species composition, the dynamics of the potato planting periods, the timing of the critical threshold with regards to the number of aphids, and the total vector intensity during the growing season. There are very few aphid vectors in the mountain zone of the Republic of North Ossetia, which is at and above an altitude of 1,650 meters above sea level. Therefore, mountain regions of this height are a natural insulator against viral infection. In the foothill zone, the most numerous aphid vectors are bean, buckthorn, and alder buckthorn-willowherb aphids, whose number varies from 35 to 280 individuals per year on a Merike trap. Keywords: potatoes, insect vectors, a Merike trap, mountain zone, spatial isolation